The Effect of Special Educational Exercises on the Performance of Some Basic skills In Volleyball For Secondary School Level - Hakmit, Asmaa (Journal of Physical Education, 2016)
The aim of the research is to identify the effect of using special exercises as educational games on the performance of some basic skills in volleyball for secondary school students. The researchers hypothesize significant statistical differences between pre and posttests in controlling and experimental groups in favor of the experimental group in posttests. The researchers used the experimental method and the subjects were (30) first stage secondary school students of Al Mustafa school. The subjects were divided into two equal groups (15) controlling and (15) experimental group. The researchers concluded that there is a great development on volleyball basic skills in the experimental group compared to the controlling group.